2022
DOI: 10.13057/biodiv/d231046
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between viruliferous Bemisia tabaci population and disease incidence of Pepper yellow leaf curl Indonesia virus in chili pepper

Abstract: Abstract. Temaja IGRM, Selangga DGW, Phabiola TA, Khalimi K, Listihani L. 2022. Relationship between viruliferous Bemisia tabaci population and disease incidence of Pepper yellow leaf curl Indonesia virus in chili pepper. Biodiversitas 23: 5360-5366. Bemisia tabaci Genn is an important pest in horticulture crops. Until today, B. tabaci has always been found in chili pepper and causes damage. In addition to a direct injury to the chili pepper, it is also the vector of Begomovirus. There is no research till date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…This might be attributed to the population fluctuation of its vector, the brown planthopper, in the field. Such fluctuations could arise due to environmental factors influencing the insect vector population (Triwidodo & Listihani, 2020;Listihani et al, 2022a;Temaja et al, 2022), as well as the cultivation pattern influencing disease distribution (Listihani et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This might be attributed to the population fluctuation of its vector, the brown planthopper, in the field. Such fluctuations could arise due to environmental factors influencing the insect vector population (Triwidodo & Listihani, 2020;Listihani et al, 2022a;Temaja et al, 2022), as well as the cultivation pattern influencing disease distribution (Listihani et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The high B. tabaci population in the field was followed by a high incidence of PepYLCIV disease, which also led to a high percentage of B. tabaci carrying begomovirus. This showed that the whitefly vector was the main cause of begomovirus transmission in the field [ 38 ]. The incidence and severity of the disease were found to be more severe in plantations with monoculture planting patterns compared to those with the intercropping pattern [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change influences the geographical distribution and population dynamics of insect pests, thereby influencing the pest status of the crop (Lehmann et al 2020;Triwidodo and Listihani 2020;Skendži'c et al 2021;Temaja et al 2022). Regarding increasing population, insects benefit from higher temperatures due to shorter reproductive maturation and increased food quality due to abiotic stress in cultivated plants (Lashari et al 2012;Blas et al 2016).…”
Section: Determination Of Tungro-virus Infection In Rice Plantsmentioning
confidence: 99%
“…In general, an increase in vector populations is followed by an increase in natural enemy populations (Temaja et al 2022). The high vector population in March and August was followed by an increase in natural enemy populations in the same month.…”
Section: Determination Of Tungro-virus Infection In Rice Plantsmentioning
confidence: 99%